You never had it [videorecording (DVD)] : an evening with Bukowski - Bizio, Silvia (Kino Lorber, 2021)
The documentary captures a raucous night of drinking and talking about sex, literature, childhood, and humanity with the cult writer Charles Bukowski in 1981. It is based on a video interview conducted by producer and journalist Silvia Bizio with Bukowski and his soon-to-be wife Linda at their home in San Pedro, California. The interview was shot on U-matic tapes, which have been digitized and edited along with new shots in Super 8 of scenes of Los Angeles today and poems read by Bukowski.